Comparative analysis of cis-regulatory elements associated with salinity and drought tolerance in rice (oryza sativa l.) using in silico analysis - Hoa, Bui Thi Hai; Duong, Nguyen Huy; Le, Dinh Thi Thu; Hang, Trinh Thi Thu; Thoa, Vu Kim; Thuy, Le Thu; Ngoc, Bui Van (Vietnam Journal of Biotechnology, 2024)
The critical roles of cis-regulatory elements (cREs) in the regulation of gene expression in response to environmental stress were reported in previous studies. Although transcription factor families to regulate gene expression in plants are well documented, there is a limited number of cREs related to salinity and drought tolerance in rice to be identified. Therefore, in this study, a comparative analysis and characterization of cREs associated with specific drought and salinity tolerance genes of rice, namely OsNHX1, OsNHX5, OsHKT1;1, OsHKT2;1, and OsSOS1, was performed using the PLACE and PlantPAN 3.0 databases, along with in silico methods. Several cis-elements within the core promoter region, including TATA-box, CAAT-box, G-box, DPE, and Y-Patch were identified. Additionally, eight other cis elements: ABRE, MYBRS, MYCRS, NAC-binding site, ACGTATERD1, GT1GMSCAM4, W-box, and DRE, were discovered and suggested to be potentially involved in drought and salinity tolerance in rice. Comparative analysis revealed that OsNHX1 and OsHKT1;1 exhibit a higher abundance of cREs compared to the other genes studied. The presence of an increased number of cREs suggests a more complex regulatory network, potentially enhancing the ability of these genes to cope with environmental stressors and fine-tune their responses to changing conditions. Furthermore, understanding the distribution and diversity of cREs across different genes can offer practical implications for genetic engineering and crop improvement strategies. Genes with desirable regulatory profiles, especially those associated with specific stress tolerances, may be prime candidates for genetic manipulation.